The Linguistic and Stylistic Features of the Monodrama “Otvetka@ua” by Neda Nezhdana (Linguostylistic Studies, 2021)
The article highlights the linguistic and stylistic features of the monodrama “Otvetka@ua” by Neda Nezhdana. It is noted that the work of the modern Ukrainian playwright is actively researched in literary criticism, but the linguistic analysis of her works is insufficiently studied. The analysis of the creative manner of Neda Nezhdana, in particular the use of the linguistic means, and the originality of their selection in the text of the  monodrama determine the topicality of the study. The peculiarities of language usage in the text under consideration are explained by the stylistics of the drama, the language of which is different from prose and poetic texts by its semantic and syntactic structure, and the relevant principles of language material selection. It is specified that the architectonics of the monodrama “Otvetka@ua” consists of continuous monologues of the main character, who feels it very essential to speak out everything connected with war and its consequences. The study has identified dominant linguistic means with which the author describes the senseless and bloody world of hybrid warfare. The authors of the article argue that “otvetka” (the answer) is the key word around which the playwright arranges the remarks and monologues of the heroine. Prevailing linguistic means to describe the hybrid war in the drama of Neda Nezhdana at the lexical level are the words related to the war, jargon, vulgarisms, slang words, exclamations, etc. Accordingly, the classification of the layers of significant lexicon of the monodrama related to war and peaceful life has been carried out. A characteristic style feature of the work under consideration at the syntactic level is the use of simple sentences, rhetorical appeals, questions, repetition of concise phrases, with the help of which the author presents the speech paradigm of the protagonist, whose life was divided into before and after the war. An indispensable attribute of drama is the remarks. Most of the remarks in the “Otvetka@ua” play contain a lot of lexemes reflecting the inner state of the main character, who is constantly reflecting with the help of music. Dominant in the author's remarks are the lexemes to denote actions related to the psychological state caused by the loss of a beloved.
Keywords: drama; linguistic analysis; vocabulary; monologue; remark